Предмет: Алгебра,
автор: AsyaGul666
Упростить выражение: 3(х+1)+(х+1)
(а-2)-2(а-2)
3х(х-2)-5х(х+3)
Ответы
Автор ответа:
0
3(х+1)+(х+1)=3x+3+x+1=4x+4
(а-2)-2(а-2)=a-2-2a+4= -a+2
3х(х-2)-5х(х+3)=3x^2-6x-5x^2-15x= -2x^2-21x
(а-2)-2(а-2)=a-2-2a+4= -a+2
3х(х-2)-5х(х+3)=3x^2-6x-5x^2-15x= -2x^2-21x
Похожие вопросы
Предмет: Математика,
автор: Uchenickkkkkkk
Предмет: История,
автор: ainagulabdilda98
Предмет: Математика,
автор: morozovskskskx
Предмет: Математика,
автор: SawFl
Предмет: Геометрия,
автор: marinka31